2016
DOI: 10.3389/fcimb.2016.00088
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Carnobacterium spp. against Listeria monocytogenes during Host Cell Invasion Using In vitro HT29 Model

Abstract: The pathogenesis of listeriosis results mainly from the ability of Listeria monocytogenes to attach, invade, replicate and survive within various cell types in mammalian tissues. In this work, the effect of two bacteriocin-producing Carnobacterium (C. divergens V41 and C. maltaromaticum V1) and three non-bacteriocinogenic strains: (C. divergens V41C9, C. divergens 2763, and C. maltaromaticum 2762) was investigated on the reduction of L. monocytogenes Scott A plaque-forming during human infection using the HT-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…A slight but a significant decrease in virulence was also observed for the ScottA strain, suggesting that the effect of the protective bacteria on L. monocytogenes virulence is strain-dependent. The effect on virulence reduction by LAB has already been described for foodborne pathogens such as L. monocytogenes ( Garriga et al, 2015 ; Pilchova et al, 2016 ) or Campylobacter ( Alemka et al, 2010 ). The effect is usually investigated as one of the probiotic properties of bacteria; however, such additional properties also increase the bioprotective value of strains and their safety assessment.…”
Section: Resultsmentioning
confidence: 96%
“…A slight but a significant decrease in virulence was also observed for the ScottA strain, suggesting that the effect of the protective bacteria on L. monocytogenes virulence is strain-dependent. The effect on virulence reduction by LAB has already been described for foodborne pathogens such as L. monocytogenes ( Garriga et al, 2015 ; Pilchova et al, 2016 ) or Campylobacter ( Alemka et al, 2010 ). The effect is usually investigated as one of the probiotic properties of bacteria; however, such additional properties also increase the bioprotective value of strains and their safety assessment.…”
Section: Resultsmentioning
confidence: 96%
“…In vitro studies have demonstrated the ability of Carnobacteriaceae, a group of bacteriocin producing lactic acid bacteria to reduce the virulence of Listeria monocytogenes on colonic epithelial cells. 78 Further, members of Carnobacteriaceae were proven to be effective as a probiotic in food-animal production 79 , 80 , 81 suggesting that they may exert a similar effect on the oral epithelial barrier. Furthermore, members of the family Bifidobacteriaceae are part of the oral commensal bacteria known to exert beneficial effects in the oral cavity and are currently being used as probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Enterocin also displays cytotoxic effects towards HT29 and HeLa cells, as a heterodimer these effects were greater. Enterocin also displayed a greater effect towards HeLa than HT29 cells [ 14 , 35 ].…”
Section: Resultsmentioning
confidence: 99%